Menyeimbangkan Pertumbuhan, Pemerataan, dan Kewilayahan: Dilema Desentralisasi dalam Pembangunan Indonesia: BPS, Institut Pertanian Bogor - Mursalin, Destrianto; Irawan, Tony (IPB University, 2025)
This research delves into the intricate dynamics of fiscal decentralization in Indonesia spanning over two decades, scrutinizing the persistent economic inequality among regions. Employing Theil and Williamson indices, the study evaluates per capita income disparages across 509 districts/cities from 2015 to 2022. Through conventional panel data analysis and spatial models including Spatial Error Model (SAM), Spatial Autoregressive (SAR), Spatial Autocorrelation Error Model (SAC), and Spatial Durbin Model (SDM), the research identifies influential factors and assesses direct and indirect impacts on per capita income. In light of the COVID-19 pandemic, the study discerns its effects by segmenting data pre- and post-pandemic. Results reveal enduring income disparities, particularly in Java and Kalimantan, with profit sharing funds (DBH) emerging as the foremost influencer. SDM exposes spatial influences, unveiling DBH's dual impact on an area's income and its adverse effects on neighboring regions. The findings underscore the imperative for nuanced fiscal decentralization policies. Recommendations advocate region-specific strategies to bridge West-East income gaps, meticulous review of DBH allocation, incentivized domestic investment, and enhanced public involvement for budgetary transparency via the Satu Data Indonesia platform. This three-pronged approach aims at fostering regional economic equilibrium and resilience.